Testing the Bacterial Cleansing Activity of the Norwex™ Microfiber Cloth - Buttafuoco, Jaclyn; Herman, Daniel P. (My University, 2019)
Bacillus subtilis and Escherichia coli are species of bacteria associated with food borne ailments. Strains of Bacillus subtilis are associated with food poisoning while a variety of strains of E. coli are associated with food-borne gastrointestinal diseases. Because of organisms such as these, maintaining proper kitchen hygiene is essential. The Norwex™ company has developed microfiber clothes that have silver nanoparticles woven in between the fibers. The company claims that the microfiber is capable of removing 99% of bacteria from surfaces and that the silver is an anti-microbial agent that will inhibit the growth of microbes in the cloth. In this study, the ability of the Norwex™ microfiber cloth to remove microbes from surfaces and inhibit microbial growth within the cloth is compared to a similar microfiber cloth that lacks the silver nanoparticles. Preliminary results using the bacterial species Bacillus subtilis and Escherichia coli do not show a significant difference between the two types of microfiber cloths in removing bacteria from surfaces nor in inhibiting the growth of microbes within the cloth. Future experiments will utilize additional species of bacteria as well as the yeast Saccharomyces cerevisiae to determine if the results obtained for these species are consistent with the results we have observed for B.subtilis and E.coli.
Color poster with text, charts, and graphs.
Keywords: Microfiber cloths; Bacterial growth; Posters